Sentidos atribuídos pelos estudantes na significação do conceito função: correspondência, relação, dependência e variação - Cervi Gabbi, Angéli; Nehring, Cátia Maria (Góndola, enseñanza y aprendizaje de las ciencias, 2021)
From the proposal of a teaching sequence, this paper aims to understand the process of learning the function concept by a group of undergraduate students. Such an approach has become necessary since the students have shown difficulties understanding that concept. We focused on an activity aiming at exploring the nucleus of the function concept – and what is meant by correspondence, relation, dependence, and variation –, by questioning: What are the main weaknesses and difficulties shown by students in an activity involving the essence of the function concept? In order to do that, we used both the Theory of Registers of Semiotic Representation and the Theory of Conceptual Fields to support this study. Data were constructed and treated through Discursive Textual Analysis, producing the following category of analysis: meanings attributed by students in the signification of the function concept: correspondence, relation, dependence, and variation. We found out that the proposed activity enabled some argumentations and discussions among students, as well as between them and the researchers. Through this interaction, the students evidenced that they mastered the conversion between the semiotic representations identified in the situation presented, thus being able to convert information into organized structures, and designing mathematical schemes to complete the proposed activity.